Catalytic CO2 esterification with ethanol for the production of diethyl carbonate using optimized CeO2 as catalyst. Issue 5 (20th January 2021) - Buchmann, Marco; Lucas, Martin; Rose, Marcus
Abstract : The direct conversion of (bio)ethanol and CO2 is a promising route to diethyl carbonate (DEC) using CeO2 from optimized catalyst synthesis procedure and cheap reactants originating from renewable resources in bioethanol production. Abstract : The direct conversion of (bio)ethanol and CO2 is a promising route to diethyl carbonate (DEC) since both reactants are cheap and originate from renewable resources in bioethanol production. In this work we present a detailed characterization and correlation between catalyst synthesis parameters and catalytic activity of pure ceria for DEC formation. An interaction between surface acidity and basicity as well as sufficiently high specific surface area is required for optimal catalytic activity which is obtained by using urea as the precipitation agent. Catalytic activity towards DEC formation is increased when adding both cerium nitrate solution and aqueous ammonia solution in a controlled manner at a pH of 10 at 50 °C for precipitation. When combining temperature-programmed desorption (TPD) experiments and catalytic testing, mainly weak basic sites appear to be relevant for the DEC formation.